2021
DOI: 10.1007/s40122-021-00310-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neuropathic Pain in Ankylosing Spondylitis: Prevalence and Characteristics

Abstract: Introduction: Pain in ankylosing spondylitis is currently considered an inflammatory pain (IP). However, it was found that some patients still had the sensation of pain even without inflammation. Our study was to investigate the prevalence and characteristics of neuropathic pain (NeP) in Chinese Han ankylosing spondylitis (AS) patients. Methods: The study consisted of three parts. Firstly, we assessed the prevalence and clinical data of NeP in 182 AS patients. Secondly, we evaluated pain improvement after etan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
2
4
1
Order By: Relevance
“…Wu et al was the first who demonstrated NP in patients with AS using neuroimaging studies in addition to the painDETECT score (4). In previous studies that used painDETECT scores, NP rates were found to be 25%-37.9% in AxSpA patients (18)(19)(20). Compared to these results, our study showed a higher NP rate of 41.7%.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Wu et al was the first who demonstrated NP in patients with AS using neuroimaging studies in addition to the painDETECT score (4). In previous studies that used painDETECT scores, NP rates were found to be 25%-37.9% in AxSpA patients (18)(19)(20). Compared to these results, our study showed a higher NP rate of 41.7%.…”
Section: Discussioncontrasting
confidence: 54%
“…VAS scores of patients with NP were twice as severe as patients without NP (23). And also higher BASDAI scores were obtained in patients with NP (20,21). In our study, pain intensity and disease activity were increased, and QoL was significantly impaired with NP presence.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have demonstrated that the prevelance of neuropathic pain is approximately 7-8% 16 . There were few studies in the literature about neuropathic pain in AS patients and the results vary (8-31% ) 5,[17][18][19] . In our study we found neuropathic pain in 35% of SpA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine and seratonin are related to pain and have a role on regulating algesic and analgesic process. Neurotransmitters have regulatory effect on local neurocytes 17,24 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 also has a key role in pain modulation in axial-SpA. Indeed, several studies showed that axial-SpA patients experience phenomena of central sensitization and neuropathic pain that may significantly worsen their quality of life [ 178 , 179 , 180 , 181 , 182 , 183 ]. A recent meta-analysis showed that in a group of 1483 AS patients, 41,5% of them had likely neuropathic pain symptoms, thus, showing the relevance of the phenomenon [ 184 ].…”
Section: Therapeutic Targets In Axial-spamentioning
confidence: 99%